Set Theory, Arithmetic, and Foundations of Mathematics : Theorems, Philosophies. - Kennedy, Juliette (Lecture Notes in Logic, 36., 2011)
A collection of remarkable papers from various areas of mathematical logic, written by outstanding members of the field.